From hashtags to ballots: Conceptualizing political influencers and evaluating their impact on election outcomes. - Carsten Schwemmer; Magdalena Riedl (PLoS ONE)
Social media influencers have evolved beyond lifestyle content, with a new subset - political influencers - rising to prominence in shaping political discourse. This paper seeks to highlight important streams of literature for defining political influencers and examining their impact on elections. We provide guidelines for conceptualizing political influencers, offering key operational definitions and decisions for future studies. Using the 2021 German federal elections as a case study, we analyze the behavior of political influencers on Instagram, focusing on the blend of political and commercial content. Our analysis reveals that political influencers shift their focus from product promotion to political messaging and support or disapproval of political entities in the lead-up to the elections. Based on post-survey election data, we further assess the relevance of influencers for voting decisions, identifying individual characteristics, such as age, associated with following influencers. We find that approximately six percent of respondents found influencer-produced content helpful in determining their voting decisions. These insights shed light on the growing importance of political influencers in electoral dynamics, providing a foundation for further exploration of their long-term political impact.